BiSpeD: Binary Spectral Disentangling applied to binary low-mass star searches - Martinez, Cristian Israel (2025)
Context. In a companion paper, we present a novel method for the spectroscopic detection of low-luminosity secondary companions of binary stars. An interesting application field is the identification of very low-mass stars as companions of late-type main-sequence stars.Aims. To provide a simple tool based on our method, we developed Binary Spectral Disentangling (BiSpeD), a Python repository that provides a toolkit for processing and analyzing spectroscopic observations. The main task of BiSpeD is find2c, which aims to calculate the mass ratio (q) of a single-lined spectroscopic binary from the analysis of a sample of observed spectra. In the same process, an estimate of the secondary effective temperature is obtained. In addition, the toolkit includes other spectral measurement tasks, including spectral disentangling and radial velocity (RV) measurement via cross-correlation.Methods. The BiSpeD package was tested on a sample of 41 late-type stars observed by the High-Accuracy Radial Velocity Planetary Searcher (HARPS). For each star in the sample, we measured the RV for the primary companion and determined the orbital parameters. We then applied the find2c task, which defines a grid of mass ratios and generates the corresponding grid of solutions that reconstruct the secondary spectrum using iterative spectral disentangling. Finally, a modified cross-correlation algorithm compares these secondary spectra with synthetic templates to find the best solution.Results. Our analysis led to the detection of 12 faint companions from the 41 candidates, including five stars below 0.3 Msun. Among our positive detections are two cases of binaries formed by a red giant primary and a main-sequence secondary. We show that reliable mass ratio values can be obtained even in cases where the orbital period is unknown and the RV amplitude is only a few km/s.